1995
DOI: 10.1111/j.1439-037x.1995.tb00208.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Biomass and Nitrogen During Plant Growth in Highly Diverging Genotypes of Winter Wheat

Abstract: Data are presented on the accumulation of nitrogen and total biomass into wheat plants at different stages in their ontogeny. Five genotypes of highly diverging origin and with widely deviating grain protein contents were cultivated at different nitrogen regimes (ranging between 0 and 150 kg N ha‐1). Growth curves as polynomials were calculated from representative subsamples of plant material collected from each plot at weekly intervals, commencing early in the vegetative stage and ending at complete maturity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The efficiency to produce dry matter in relation to the amount of absorbed nitrogen was distinctly lower in the high-protein genotypes Goertzen 5559 and Frontiersman than in the genotypes with normal GPG (Table 5). According to the results presented in the previous communication (BERTHOLDSSON and STOY 1995) only small differences in dry matter production could be found between the genotypes before anthesis but very significant ones dunng the grain filling period. Nitrogen present in above-ground parts was thus not utilized for grain dry matter production to the same extent in the high-protein genotypes as in the types with normal GPG.…”
Section: Nitrogen Utilizationmentioning
confidence: 65%
See 2 more Smart Citations
“…The efficiency to produce dry matter in relation to the amount of absorbed nitrogen was distinctly lower in the high-protein genotypes Goertzen 5559 and Frontiersman than in the genotypes with normal GPG (Table 5). According to the results presented in the previous communication (BERTHOLDSSON and STOY 1995) only small differences in dry matter production could be found between the genotypes before anthesis but very significant ones dunng the grain filling period. Nitrogen present in above-ground parts was thus not utilized for grain dry matter production to the same extent in the high-protein genotypes as in the types with normal GPG.…”
Section: Nitrogen Utilizationmentioning
confidence: 65%
“…It may also be noticed that Goertzen 3539 and Frontiersman boch exhibited very high numbers of ears per m" but that this trait was counteracted by low numbers of grain per ear to such an extent that the resulting numbers of grains per m^ turned out to be distinctly lower than those of the two best Swedish genotypes. Since numbers of grains per ear as well as 1000-grain weights are determined late in the course of ontogenetic development, the relatively low production of photoassimilates around and after anthesis in Goertzen 5559 and Frontiersman, described in the previous communication (BERTHOLDSSON and STOY 1995), appears to be a major reason for the low values of these parameters and hence also of grain yield.…”
Section: Yield Componentsmentioning
confidence: 92%
See 1 more Smart Citation
“…However, it is less clear whether modern cultivars perform better in limited N conditions. Bertholdsson and Stoy (1995a) and Foulkes et al (1998) found that the most recent cultivars were adapted to higher levels of N and took up relatively more N from fertilizer, whereas the older cultivars had a relatively large uptake of N mineralized from soil. Early vigorous growth has also been suggested as a major factor influencing N uptake in modern wheat lines (Liao et al 2006).…”
Section: Nitrogen Use Efficiencymentioning
confidence: 99%
“…Results from additional analyses indicated that improvements were consistent and significant over time (Table 8), demonstrating the important role of plant breeding and cultivar selection in improving the balance between applied and harvested N, thereby reducing the N leaching risk. Bertholdsson and Stoy (1995) and Foulkes et al (1998) also reported that the most recent cultivars were adapted to higher fertilizer application N rates and they took up relatively more N from fertilizer compared with older cultivars. Improved yields were associated with genetic improvements in YRN and N 2009b).…”
Section: Discussionmentioning
confidence: 99%